Chemical composition and pharmacological mechanism of Qingfei Paidu Decoction and Ma Xing Shi Gan Decoction against Coronavirus Disease 2019 (COVID-19): In silico and experimental study - Yang, Ruocong; Liu, Hao; Bai, Chen; Wang, Yingchao; Zhang, Xiaohui; Guo, Rui; Wu, Siying; Wang, Jianxun; Leung, Elaine; Chang, Hang; Li, Peng; Liu, Tiegang; et al. (Pharmacological research, 2020)
[Display omitted] •A total of 129 compounds of QFPD were dissected by UPLC-MS and molecular networking of MS data.•COVID-19 disease network was constructed to generate the QFPD therapeutic network based on chemical constituents and target prediction.•Toll-like signaling pathway was found to be important pathway regulated by QFPD.•Transcriptomic analysis revealed MXSG Decoction regulated multiple complement, coagulation cascades and thrombin system to interfere infection. The Coronavirus Disease 2019 (COVID-19) pandemic has become a huge threaten to global health, which raise urgent demand of developing efficient therapeutic strategy. The aim of the present study is to dissect the chemical composition and the pharmacological mechanism of Qingfei Paidu Decoction (QFPD), a clinically used Chinese medicine for treating COVID-19 patients in China. Through comprehensive analysis by liquid chromatography coupled with high resolution mass spectrometry (MS), a total of 129 compounds of QFPD were putatively identified. We also constructed molecular networking of mass spectrometry data to classify these compounds into 14 main clusters, in which exhibited specific patterns of flavonoids (45 %), glycosides (15 %), carboxylic acids (10 %), and saponins (5 %). The target network model of QFPD, established by predicting and collecting the targets of identified compounds, indicated a pivotal role of Ma Xing Shi Gan Decoction (MXSG) in the therapeutic efficacy of QFPD. Supportively, through transcriptomic analysis of gene expression after MXSG administration in rat model of LPS-induced pneumonia, the thrombin and Toll-like receptor (TLR) signaling pathway were suggested to be essential pathways for MXSG mediated anti-inflammatory effects. Besides, changes in content of major compounds in MXSG during decoction were found by the chemical analysis. We also validate that one major compound in MXSG, i.e. glycyrrhizic acid, inhibited TLR agonists induced IL-6 production in macrophage. In conclusion, the integration of in silico and experimental results indicated that the therapeutic effects of QFPD against COVID-19 may be attributed to the anti-inflammatory effects of MXSG, which supports the rationality of the compatibility of TCM.